Occurrence of multiple genotype infection caused by Leishmania infantum in naturally infected dogs. - Elisa Cupolillo; Amanda S Cavalcanti; Gabriel Eduardo Melim Ferreira; Mariana Côrtes Boité; Fernanda Nazaré Morgado; Renato Porrozzi (Public Library of Science (PLoS), 2020)
Genetic polymorphisms in natural Leishmania populations have been reported in endemic areas. Microsatellite typing is a useful tool to elucidate the genetic variability of parasite strains, due to its capability for high-resolution mapping of genomic targets. The present study employed multilocus microsatellite typing (MLMT) to explore the genotypic composition of Leishmania infantum in naturally infected dogs by genotyping parasites infecting different tissues with or without in vitro expansion. Eighty-six samples were collected from 46 animals in an endemic region of visceral leishmaniasis (VL). MLMT was performed for 38 spleen samples and 48 L. infantum cultures isolated from different tissues. Of the 86 samples, 23 were effectively genotyped by MLMT, identifying nine multilocus genotypes (MLG; referred to as MLG A-I). MLGs A, B and C were detected in more than one type of tissue and in more than one sample. Conversely, MLG D-I were uniquely detected in one sample each. The results showed that multiple genotype infections occur within a single host and tissue. Paired sample analysis revealed the presence of different MLMT alleles in 14 dogs, while the same MLG allele was present in 15 animals. STRUCTURE analysis demonstrated the presence of two populations; 13 samples displayed a similar admixture of both ancestral populations, and these were not assigned to any population. Only samples for which Q ≥ 0.70 after CLUMPP alignment were considered to be part of Population 1 (POP1) or Population 2 (POP2). POP2 comprised the majority of samples (n = 54) compared to POP1 (n = 19). This study presents evidence of multiple genotype infections (caused by L. infantum) in dogs in an area with high VL transmission. Further investigations must be undertaken to determine the effects of multiple infection on the host immune response and disease dynamics and treatment.